Expression level of CD117 (KIT) on ovarian cancer extracellular vesicles correlates with tumor aggressiveness - Shnaider, Polina V.; Petrushanko, Irina Yu.; Aleshikova, Olga I.; Babaeva, Nataliya A.; Ashrafyan, Lev A.; Borovkova, Ekaterina I.; Dobrokhotova, Julia E.; Borovkov, Ivan M.; Shender, Victoria O.; Khomyakova, Elena (Frontiers in Cell and Developmental Biology, 2023)
Ovarian cancer is known to be the most lethal malignancy among all gynecological cancers affecting a large number of women worldwide. The treatment of ovarian cancer is challenging due to the high recurrence rate of the disease and is further complicated by acquired chemoresistance. Most ovarian cancer deaths are the result of the metastatic spread of drug-resistant cells. The theory of cancer stem cells (CSC) suggests that both tumor initiation and progression are driven by undifferentiated stem cells capable of self-renewal and tumor initiation and development of chemoresistance. The CD117 mast/stem cell growth factor receptor (KIT) is the most commonly used marker for ovarian CSCs. Here, we analyze the correlation between CD117 expression and histological tumor type in ovarian cancer cell lines (SK-OV-3 and MES-OV) and in extracellular vesicles (EVs) isolated from the urine of ovarian cancer patients. We have demonstrated that the abundance of CD117 on cells and EVs is fully correlated with tumor aggressiveness and treatment resistance status and inversely correlated with expression level of EpCam. Moreover, using EVs isolated from ovarian cancer ascites, it was shown that relapse disease is characterized by a much higher expression of CD117 than primary tumor.